Comparison analysis of Altman's and Foster's Z-score model in predicting bankruptcy: evidence from Indonesian automotive and component industries - Wahyudi Nurmansyah; Afdal Mazni; F Febriyanto (Diponegoro International Journal of Business, 2021)
The purpose of this study is to determine differences in bankruptcy predictions of the Altman and Foster models. The sampling technique used is purposive sampling with an observation period of 2016-2018 with 12 company samples per year. The analysis technique uses the Altman and Foster method with the paired two-sample t-test as a hypothesis test tool. Based on the results of the Altman and Foster Z- Score model of automotive and component industries in 2016-2018 it can be concluded that the financial model of Altman and Foster can predict bankruptcy. Furthermore, the hypothesis testing found that there is no differences in the results of the Altman and Foster bankruptcy prediction.